Peran Penalaran Moral Sebagai Mediator Pengaruh Iklim Etis Organisasi Terhadap Integritas Karyawan - Idha Rahayuningsih (Universitas Muhammadiyah Gresik, 2025)
Background: Several previous studies have proven the role of moral reasoning as an important determinant for someone to make ethical decisions and ethical behavior in organizations. Meanwhile, the ethical climate of the organization can affect the process of moral reasoning which is then translated into ethical behavior. Objective: Therefore, this study aims to determine the mediating role of moral reasoning on the influence of organizational ethical climate on employee integrity. Sampling with incidental sampling technique. Method: It was found that 101 employees were willing to fill out a questionnaire via google.form. Data is collected through an ethical integrity scale that refers to the Du Toit concept. (2015); Defining Issues Test (DIT) developed (Rest, 1979) and organizational ethical climate scale developed (Victor and Cullen, 1987). Data analysis used the SmartPLS 4 application which included measurement model analysis, good fit model testing, and structural model analysis. Result: The results of the analysis show the role of law-oriented moral reasoning and social order as a partial mediator on the effect of organizational ethical climate on integrity.